Economic Neglect as Domestic Violence: Analysis of Divorce Decisions from Fatima Mernissi's Islamic Feminist Perspective - Susantin, Jamiliya; Rijal, Syamsul; Jannah, Sofiatul; Himsyah, Fatroyah Asr; Habiburrahman, Muhammad (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study explores economic neglect as a dimension of domestic violence within Indonesian divorce cases, analyzed through the lens of Fatima Mernissi’s Islamic feminist framework. Mernissi’s framework is particularly relevant in Muslim-majority contexts, as it critically challenges patriarchal interpretations of Islamic legal norms that continue to shape family law adjudication. Using a qualitative design that integrates juridical-normative and socio-legal approaches, the study analyzes 16 divorce decisions issued by five Religious Courts in Indonesia between 2016 and 2025. The findings reveal that economic neglect never occurs in isolation: 100% of cases intersect with other forms of violence, including psychological, physical, and social abuse. Three patterns of economic neglect are identified: total neglect (37.5%), partial neglect (43.75%), and neglect accompanied by economic exploitation (18.75%). However, only 18.75% of the cases culminated in the imposition of full economic sanctions, reflecting the limited enforcement of women’s economic entitlements. Significant regional disparities were also found, with courts in East Java demonstrating greater consistency than those in other regions. The study proposes legal reforms, including explicit recognition of economic neglect as an autonomous form of domestic violence in Article 9 of the Act of the Republic of Indonesia Number 23 of 2004 concerning the Domestic Violence Elimination Law (UU PKDRT) and reformulation of Articles 80 and 84 of the Compilation of Islamic Law (KHI). These reforms are intended to reinforce enforceable post-divorce economic responsibilities, advance substantive justice, and foster greater consistency in judicial practice at the national level.